2015
DOI: 10.18632/oncotarget.5818
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes enriched in stemness/metastatic-related mRNAS promote oncogenic potential in breast cancer

Abstract: Cancer cells efficiently transfer exosome contents (essentially mRNAs and microRNAs) to other cell types, modifying immune responses, cell growth, angiogenesis and metastasis. Here we analyzed the exosomes release by breast tumor cells with different capacities of stemness/metastasis based on CXCR4 expression, and evaluated their capacity to generate oncogenic features in recipient cells. Breast cancer cells overexpressing CXCR4 showed an increase in stemness-related markers, and in proliferation, migration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 24 publications
2
59
0
1
Order By: Relevance
“…Recently, Figueroa et al, has reported that glioma associated-human MSCs (GA-hMSCs)-derived EVs facilitate tumor supporting activities of GSCs by transferring glioblastoma specific miR-1587 between cells (91). Additionally, the comparison of miRNA content of EVs isolated from breast patients revealed stem cell-like properties and metastatic signature from patients with worse prognosis (92). This data supports the view that cancer cells with stem-like properties and their EVs could potentially aggravate tumor progression and metastasis.…”
Section: Networking Between Stem-like Cells' Subpopulations: Heterogesupporting
confidence: 72%
“…Recently, Figueroa et al, has reported that glioma associated-human MSCs (GA-hMSCs)-derived EVs facilitate tumor supporting activities of GSCs by transferring glioblastoma specific miR-1587 between cells (91). Additionally, the comparison of miRNA content of EVs isolated from breast patients revealed stem cell-like properties and metastatic signature from patients with worse prognosis (92). This data supports the view that cancer cells with stem-like properties and their EVs could potentially aggravate tumor progression and metastasis.…”
Section: Networking Between Stem-like Cells' Subpopulations: Heterogesupporting
confidence: 72%
“…In addition, exosomes may provide a non-invasive means to assess cancer pathogenesis, progression, and treatment outcomes. Recently, the exosome-shuttling miRNA [73-75], lncRNA [76] and proteins [77] have been demonstrated to be closely related to the prognosis of a variety of tumors, including esophageal cancer, ovarian cancer, lung cancer, bladder cancer, breast cancer and so on [73-78]. These investigations demonstrate the applicability of exosomes as biomarkers of cancer prognosis to sarcoma pateints.…”
Section: Roles Of Exosomes In Sarcomamentioning
confidence: 99%
“…In summary, EVs function as major immune regulators, and profiling of circulating EVs has high potential as marker for immunogenicity. Profiling of EVs circulating in BC patients' blood is common [125][126][127][128][129] but major issues remain regarding a validated and standardized isolation procedure, which have to be solved before the clinical implementation of EVs is attainable [115].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%